IMPACT OF UNDERGROUND ECONOMY UPON THE ROMANIAN ECONOMY - Sorin-Daniel, Manole (Strategii Manageriale, 2012)
The present article shows estimates the size of underground economy in Romania during 1999 - 2012 (as a percentage of real GDP), carried out by Schneider by means of the MIMIC method. Moreover, the data on 2011 referring to this phenomenon are compared to the data on 30 different states in Europe. In addition, in order to emphasize the difficulty of the scientific endeavour of evaluating the size of the underground economy and especially to see what the endeavour is basically about, the MIMIC methodology has been shaped which is the procedure most frequently used by Schneider in his latest surveys. Using a linear regression model in the end of this article helps accomplish a prognosis of the size of Romania’s underground economy in 2013.